Pengaruh Strategi Pemasaran Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Pada PT Narindo Solusi Telekomunikasi Tap Lotu (LPPM Universitas HKBP Nommensen, 2025)
This research aims to analyze the influence of marketing strategies and service quality on consumer purchasing decisions at PT Narindo Solusi Telekomunikasi Tap Lotu. The research method used is quantitative with a causal approach. Data were collected through questionnaires distributed to consumers. Data analysis techniques include multiple linear regression analysis, T-test, F-test, correlation coefficient, and determination. The research results show that marketing strategy (t = 3.223, sig = 0.002) and service quality (t = 5.754, sig = 0.000) have a significant effect on purchasing decisions. Simultaneously, marketing strategy and service quality significantly influence purchasing decisions (F = 35.878, sig = 0.000) with a coefficient of determination (R Square) of 0.503. This research concludes that marketing strategies and service quality play an important role in enhancing consumer purchasing decisions. PT Narindo is advised to maintain and improve marketing strategies and service quality with a focus on consumer needs and expectations.